Impact of high-speed shear homogenization pretreatment on structure, functional characteristics, and interfacial properties: A case of Rice Glutelin - Zhuangpeng Wang; Zhangtao Chen; Lufan Tan; Jin Tu; Yong Sun; Yuanping Ye; Senwang Zhang; Leiyan Wu (Food Chemistry: X)
In this study, rice glutelin (RG) was pretreated using high-speed shear homogenization (HSSH) to enhance its functional characteristics and interfacial properties through structural modification. Its structure was characterized using techniques such as SDS-PAGE, FT-IR, SEM, interface analyzer, dynamic and electrophoretic light scattering. The results indicated that HSSH preserved the primary structure of RG but significantly affected its secondary structure. It increased the surface hydrophobicity and conformational flexibility, enhanced electrostatic repulsion, reduced the particle size, and produced a loose and porous microstructure. These alterations resulted in variations in the functional and interfacial properties of RG. After HSSH treatment at 12,000 rpm for 2 min, RG exhibited optimal improvements in solubility (5.56 %), WHC (6.00 g/g) and OHC (2.20 g/g), EAI (10.19 m2/g) and ESI (341.98 min), as well as FC (16.20 %) and FS (64.21 %). However, excessive HSSH treatment induced the formation of aggregates, which is detrimental to the improvement of these properties.